FR1.1: Gender mainstreaming from an institutional perspective: Cases of small and micro irrigation projects in Ethiopia - Nigussie, Likimyelesh; Minh, Thai Thi; Schmmiter, Petra (International Water Management Institute, 2022)
Achieving gender equality in irrigation can result in greater production, income and job opportunity, whilst building climate resilience in the sub-Sahara Africa. To aid integration of gender in the planning and implementation of irrigation programs, national irrigation agencies, donors, and researchers have been assisting project implementers to formulate a gender mainstreaming strategy. However, as efforts to close gendered gaps in irrigation has been increasing, little is known about how interaction among institutions at different scales determine success of gender mainstreaming strategies. The study presents a qualitative analysis of how multi-level institutional context shape success of gender mainstreaming strategies by examining nine small and micro irrigation development projects in Ethiopia. Specifically, it analyzed how rules, roles and capacities shape gender mainstreaming strategy in different irrigation development projects. Results show that ‘rule-based' strategy adopted by small scheme-based irrigation projects, that emphasizes policies and rules to equal rights and opportunities to participate in development and decision making, and capacity development of individuals and institutions. Also, results show ‘role-based' strategy adopted by project promoting small and micro irrigation technologies that focus on challenging social norms to address the issue of power and workload imbalance and developing capacity of actors including farmers. Both strategies prescribe certain numbers for women and deploy participatory approaches to ensure gender equality. However, negative stereotypical perceptions about women by family, community, and the private sector militate against the success of gender mainstreaming. Further, institutional biases and limited capacities reproduce gender inequality by reinforcing stereotypical gender norms. This implies, enhancing the success of gender mainstreaming strategies call for a holistic approach that facilitate transformative change at different scale through broad based partnership between actors at scale.